Sight, sound, motion applied media aesthetics - Zettl, Herbert (Wadsworth series in broadcast and production, 2011)
Describes the major aesthetic image elements--light and color, space, time/motion, and sound--and presents in-depth coverage of how they are creatively used in television and film.